Zhodnocení hospodaření a fundraisingu vybrané neziskové organizace - Štraubová, Veronika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2023)
Bakalářská práce je zaměřena na zhodnocení hospodaření a fundraisingových aktivit vybrané nestátní neziskové organizace s názvem Dobrovolnické centrum Kladno, z.s. V teoretické části bakalářské práce je uveden popis problematiky neziskového sektoru a fundraisingu za pomocí vybrané literatury. V analytické části je provedena analýza nákladů a výnosů spolu s modifikovanou finanční analýzou. Na základě těchto analýz je zhodnocen vývoj hospodaření a fundraisingu. Poslední část práce je věnována vlastním návrhům na zlepšení nedostatků.

The bachelor thesis focuses on economic evaluation and fundraising activities of selected non-governmental non-profit organization called Dobrovolnické centrum Kladno.In the theoretical part of the bachelor's thesis there is a description of the issues of the non-profit sector and fundraising which is presented on the basis of selected literature. In the analytical part of the bachelor's thesis there is an analysis of costs and revenues and modified financial analysis. Based on these analyses there is a summary of development of the economy and fundraising. The last part of the bachelor's thesis is dedicated to own proposals for improving weaknesses.
Evaluation of Economy and Fundraising of Selected Non Profit Organization
Keywords: nestátní nezisková organizace; modifikovaná finanční analýza; fundraising; náklady a výnosy; non-governmental non-profit organization; modified financial analysis; fundraising; costs and revenues